Testing purity of commonly used marketed insecticides collected from different regions of Bangladesh (Asian Journal of Medical and Biological Research, 2017)
The study was made on testing purity of different marketed brands of three insecticide groups such as quinalphos, malathion and fenitrotion in the Pesticide Analytical Laboratory under Division of Entomology, Bangladesh Agricultural Research Institute (BARI), Gazipur using suitable protocols GC-FID. Nineteen marketed brands of these insecticides collected form dealers or retailers of Jessore, Gazipur and Rangpur region were analyzed and estimated their purity in two seasons of 2006-2007 and 2007-2008. In these two seasons, among five marketed brands of Malathion, only one brand (MTF) had 98.95-100% purity which was collected from Jessore in 2007-08 and Gazipur in both the seasons and considered to be standard or acceptable product, but in other regions, this brand contained less AI and was found to be